Bioelectrical Impedance Vector Analysis and Muscular Fitness in Healthy Men - Rodríguez-Rodríguez, Fernando; Cristi-Montero, Carlos; González-Ruíz, Katherine; Correa-Bautista, Jorge; Ramírez-Vélez, Robinson (Nutrients, 2016)
Muscle strength can define the general muscular fitness (MF) measurable through hand-grip strength (HG), which is a factor that relates to the health of people of different ages. In this study we evaluated the muscle strength together with a bioimpedance electric analysis in 223 healthy Colombian adult subjects. The bioelectrical impedance vector analysis (BIVA) was conducted to determine the resistance (R), reactance (Xc) and phase angle (PhA). We classified the subjects into three groups (for tertiles), obtaining lower values of R and Xc in subjects with lower HG, plus a high correlation between PhA and HG. An increase in the level of PhA is associated with a high level of MF in a sample of healthy Latin American adult men. The BIVA’s parameters and PhA are a potentially effective preventive measure to be integrated into routine screening in the clinical setting.